EFFECT OF GRIP SIZE AND GRIP STRENGTH ON PISTOL MARKSMANSHIP IN POLICE OFFICERS: A PILOT STUDY - Orr, Robin M.; Rofe,; Hinton, Ben; Dawes, Jay; Greco, Gianpiero; Lockie, Robert (NBP. Nauka, bezbednost, policija, 2021)
Background: Police officers may be required to use their firearms in self-defence. The purpose of this study was to evaluate the relationships between hand grip size and strength on pistol shooting accuracy in police officers. Methods: Twelve (age = 38.08±6.24 years; height = 174.42±7.33 cm) police officers had their hand sizes (palm width and hand span) and hand grip strength measured. Handgrip dynamometer was set at a Glock 17 pistol’s grip width (50mm). The officers fired 10 rounds from their service pistols at a stationary target. Independent samples t-tests were performed to identify differences between the sexes. Correlations were used to investigate relationships between measures of hand size, strength, and marksmanship. Alpha levels were set at p